2013
DOI: 10.1111/resp.12086
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids increase alveolar epithelial permeability via mitogen‐activated protein kinase, cytosolic phospholipase A2, cyclooxygenase‐2, prostaglandin E2 and junctional proteins

Abstract: Background and objective: Bile acid (BA) aspiration is associated with various lung diseases. It was hypothesized that BA may induce changes in alveolar epithelium permeability and contribute to the pathogenesis of lung injury. Methods: Human alveolar epithelial cells were grown in monolayer and stimulated with a major component of BA, chenodeoxycholic acid (CDCA). Transepithelial electrical resistance (TER) and paracellular fluxes were measured to assess permeability alteration. Prostaglandin E2 (PGE2) produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Similar to previous reports (6,7), our data also demonstrated the overexpression of COX-2 in small airways of COPD lungs. It has been reported that the bile acid CDCA promotes COX-2 expression in primary human alveolar epithelial cells (11), and FXR mediates bile acid-induced COX-2 expression in esophageal cancer cell lines (34). We further investigated whether bile acid also could induce COX-2 in airway epithelial cells and if FXR was involved in this process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to previous reports (6,7), our data also demonstrated the overexpression of COX-2 in small airways of COPD lungs. It has been reported that the bile acid CDCA promotes COX-2 expression in primary human alveolar epithelial cells (11), and FXR mediates bile acid-induced COX-2 expression in esophageal cancer cell lines (34). We further investigated whether bile acid also could induce COX-2 in airway epithelial cells and if FXR was involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Gastroesophageal reflux disease (GERD) is recognized as a potential risk factor for exacerbation of COPD (29) and the bile acid aspiration has been reported to induce lung injury by promoting COX-2 expression in human alveolar epithelial cells (11). Therefore, we next explored whether FXR activation could regulate the bile acid-induced COX-2 expression in HBE cells.…”
Section: Overexpression Of Fxr Regulates the Bile Acid-induced Cox-2 mentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of BA on paracellular permeability in pathophysiological conditions has been scarcely studied, and is generally viewed as deleterious, increasing paracellular passage in intestinal 83 and respiratory epithelial cells 84 . However the precise signal transduction mechanisms, in particular the BA receptors involved, were not investigated in these studies.…”
Section: Tgr5‐dependent Protective Responses Against Ba Overloadmentioning
confidence: 99%
“…Recent data suggest that elevated levels of bile acids and pepsin in bronchoalveolar lavage fluid (BALF) and sputum are effective biomarkers for diagnosis and treatment of gastropulmonary aspiration . Bile acid aspiration has been implicated in lung injury and airway fibrosis . The presence/concentration of bile acids in BALF has been correlated with the degree of lung fibrosis in patients with IPF, suggesting bile acid microaspiration may be an active player in the development and/or progression of IPF.…”
Section: Introductionmentioning
confidence: 99%